2021
DOI: 10.1155/2021/8711286
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of AQP2 and HSP70 in Broiler Kidney Tissue Treated with Salix tetrasperma Roxb. Extract under Heat Exposure

Abstract: The administration of plant extracts to broilers may be a way to mitigate the effects of heat stress. The importance of AQP2 and HSP70 compounds in maintaining the homeostasis of the chicken body when it is subjected to heat stress is well established. This study aims to determine the effect of giving the ethanolic extract of the leaves of Salix tetrasperma Roxb. on the immunohistochemical expression of AQP2 and HSP70 in exposed and unexposed broiler kidney tissue. This study used 36 samples of 28-day-old chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Research has shown that after exposure to 37°C ± 1°C for 5 h, broilers may resist heat stress by upregulating the expression of HSP60 in the heart ( Yan et al, 2009 ). Sugito et al (2021) found that chronic cold stimulation can significantly upregulate the expression of HSP70 in the heart of the Huainan ephedra chicken. We found that the protein expression levels of HSPs in the CS group before ACS were significantly higher than those in the CC group, indicating that the expression of HSPs could be regulated during cold exposure to protect the structural integrity of heart tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Research has shown that after exposure to 37°C ± 1°C for 5 h, broilers may resist heat stress by upregulating the expression of HSP60 in the heart ( Yan et al, 2009 ). Sugito et al (2021) found that chronic cold stimulation can significantly upregulate the expression of HSP70 in the heart of the Huainan ephedra chicken. We found that the protein expression levels of HSPs in the CS group before ACS were significantly higher than those in the CC group, indicating that the expression of HSPs could be regulated during cold exposure to protect the structural integrity of heart tissue.…”
Section: Discussionmentioning
confidence: 98%
“…The involvement of Aquaporins (AQPs) in the transport of water and glycerol across various tissues has been observed in several animal species, including sheep ( Sugito et al 2021). Aquaporins (AQPs) constitute a family of ~ 28 kDa transmembrane proteins that distributed throughout diverse tissues and facilitate bidirectional water transport across cell membranes to ful ll physiological requirements (Verkman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock proteins (HSPs) protect organisms from various types of stresses and serve as indicators of injury in the animal stress response system [23,24]. For instance, HSP70 aids in the proper folding of nascent peptide chains and the repair of misfolded proteins under various stresses, thereby increasing stress tolerance in animals [25].…”
Section: Introductionmentioning
confidence: 99%